Bart Syndrome: A Deceptively Scary Presentation - Madhvi Trivedi; Rajesh Dutt Mehta; Bhikam Chand Ghiya; Prasoon Soni (Wolters Kluwer Medknow Publications, 2023)
Background: Bart syndrome is one of the rarest forms of aplasia cutis congenita (ACC). Clinical Description: We report a sporadic case of a neonate presenting with the absence of skin on the lower limb, tense blisters on fingers, and nail dystrophy. Management: Clinical features and skin biopsy confirmed the diagnosis of Bart syndrome. The baby was given symptomatic treatment with regular antimicrobial dressing. Within 2 weeks, the defect healed with the formation of hypopigmented scar and milia. The bullous lesions also disappeared completely. Conclusion: Bart syndrome, which is a type of ACC, is an extremely rare occurrence. Although it has an extensive involvement, the lesions if superficial, limited to the epidermis, have a good prognosis. Conservative management is sufficient to cause healing within a short span of time.